PEROLEHAN SUHU AIR PENDINGIN PRIMER REAKTOR TRIGA 2000 KETIKA PENAMBAHAN CEROBONG DAN PELAT PENUKAR PANAS - Reinaldy (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Continuation of the TRIGA 2000 reactor operation is determined by the fuel and primary cooling water temperature. For example, recently the TRIGA 2000 reactor is very difficult to reach the maximum power level of 2000 kW, because at maximum power level, the maximum fuel temperature in the reactor core is 675 oC, the inlet primary cooling water temperature into reactor core is 41.3 oC, and the outlet primary cooling water from reactor tank is 48.2 oC. The increasing of the fuel temperature and primary cooling water temperature in reactor core, increase also the bubbling and the bubble of vapour in the reactor core so, it reduces the neutrons moderation in the reactor core and then the reactor is unable to reach power level of 2000 kW. There are some actions can be done to reduce the fuel temperature and the primary cooling water temperature in reactor core, as to give a chimney above reactor core and to add additional heat exchanger plates. Because these studies can not be done experimentally, then the analysis done through theoretical studies using computer programs RELAP5/Mod3.2. Based on result of the study, it is known that by rising the chimney height to become 2 m, give additional heat exchanger plates to become 384 slabs, flow rate of primary cooling water is 950 gpm, and to increase flow rate of secondary cooling water to become 1200 gpm, it can reduced the primary cooling water temperature exit from heat exchanger or the primary cooling water temperature into reactor core to become 30.48 oC. If this condition applied, it can reduce the fuel cladding and the primary cooling water maximum temperature in reactor core, so the bubbling decreased in the reactor core, though it will increase the maximum concentration of N-16 on the tank surface to become 49.41%.